Foreign Direct Investments, Regional Incentives and Regional Attractiveness in Greece - Aikaterini Kokkinou; Ioannis Psycharis (European Regional Science Association (ERSA), 2004)
The aim of this paper is to analyze the Foreign Direct Investment (FDI) activity in Greece. The paper starts with defining the main FDI terms and giving a general literature review corresponding to the FDI allocation. Then, there is a description of recent trends in FDI activity both worldwide and Greece. Especially FDI investments in Greece are analyzed presenting the magnitudes of inflows, outflows, inward stock, outward stock, as well as foreign mergers and acquisitions, in terms of sales and purchases. The second part of the paper describes the regional and sectoral allocation of FDI in Greece, emphasizing whether the investment incentive scheme contributes to the attraction of FDI in specific regions, or the growth rate of each region is the main motive for locating foreign investment capital. The analysis is based on the most recent statistical data covering magnitudes until 2002.
Keywords: 330